Flail Chest: Influence on Length of Stay and Mortality in Blunt Chest Injury. Issue 9 (September 2018) - Udekwu, Pascal; Roy, Sara; McIntyre, Sarah; Farrell, Meagan
Flail chest is used as one of the indicators for rib fixation, which is being performed more frequently. Radiologic and clinical flail chest are not clearly differentiated in published studies and the relationship between radiologic flail chest (RFC) and outcomes are not clearly established. Our study was designed to evaluate the relationship of RFC to outcomes in patients with severe blunt chest injury. Adult patients with severe blunt chest injury admitted between January 1, 2014, and June 30, 2016, were identified retrospectively. Three hundred and eighty-three patients were studied and mortality rate was not significantly different in patients with an RFC diagnosis (5.88%) compared with patients without RFC (3.83%), P = 0.50. Length of stay (LOS) in patients with and without RFC were compared and patients with RFC were found to have a statistically significant increase in both hospital and intensive care unit LOS (P = 0.0178, P < 0.0017). Multivariate analysis confirmed RFC as an independent predictor of increased LOS when compared with the number of rib fractures and displacements. Our study suggests that RFC may drive inappropriate use of rib fixation. This questions the justification of liberal rib fixation based on the perceived high mortality rate of modern flail chest diagnoses.